Characteristics of SrBi2Ta2O9 thin films fabricated by the RF magnetron sputtering technique - Lee, JK; Song, TK; Jung, HJ (TAYLOR & FRANCIS LTD, 1997)
SBTO thin films were successfully fabricated by r.f. magnetron sputtering deposition. Bismuth content exists mainly in the form of (Bi2O2)(2+) at the surface and the elemental bismuth forms at the interface between the SBTO layer and the Pt electrode. The crystal structure of SBTO films grown on the Pt(lll) layer were preferentially c-axis oriented. The Pt/SBTO/Pt capacitor shows P*r-P(boolean AND)r=16.3 mu C/cm(2) and Ec=50kV/cm.
Keywords: FERROELECTRIC CAPACITORS; FATIGUE; ELECTRODES